Karateristik Tegangan Tembus Gas Argon (Ar) Dengan Tegangan Tinggi Arus Bolak-Balik - M Javad Faruqi; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In electric power systems, there are many aspects that must be considered for its operation that is, conductors, insulators, and other electrical system equipment. Especially on insulators, good insulation quality is required to ensure reliability and quality of electric power distribution to consumers. In industrial gas insulation is often used because of its dielectric strength is greater than the other isolation. In general the gas insulation used SF6, N2, and CO2 has good dielectric strength. In this study, the author tries to test the isolation of another alternative gas that is in the form of argon gas. In the test of this research aims to enrich the treasury of the data from testing the penetrating tension with argon gas isolation and as a preliminary study of argon gas isolation in the test of penetrating voltage with high-voltage AC. Tests conducted using variations of electrodes and gas pressure as much as 20 times the test so that the results obtained in the form of breakdown voltage and air correction factor. Keywords: Argon, Electrode, Breakdown Voltage, High Power Plant AC, Air Correction Factor